Design of a Miniature Plastic Waste Pyrolysis Machine Prototype Based on a Used Oil Burner with a Simple Condensation System - Komarudin Komarudin; Arief Rachman; Denny Purmanto (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to design, realize, and evaluate the performance of a mini-scale plastic waste pyrolysis machine prototype based on a used oil burner with a simple condensation system. The research methods include design, fabrication of main components, system assembly, and thermal performance testing for 60 minutes. Test results show that the reactor reached a maximum temperature of 346°C at 40 minutes and maintained a stable temperature of around 325°C. The spiral condensation system was able to convert pyrolysis vapor into liquid oil. The developed prototype has the potential to be an alternative mini-scale waste-to-energy plastic waste treatment technology that is economical and applicable.